The effect of ocean heat flux on seasonal ice growth in Young Sound (Northeast Greenland). Issue 7 (14th July 2015) - Kirillov, Sergei; Dmitrenko, Igor; Babb, David; Rysgaard, Søren; Barber, David
Abstract The seasonal ice cover plays an important role in the climate system limiting the exchange of heat and momentum across the air‐water interface. Among other factors, sea ice is sensitive to the ocean heat flux. In this study, we use in situ oceanographic, sea ice, and meteorological data collected during winter 2013/2014 in Young Sound (YS) fjord in Northeast Greenland to estimate the ocean heat flux to the landfast ice cover. During the preceding ice‐free summer, incident solar radiation caused sea surface temperatures of up to 5–6°C. Subsequently, this heat was transferred down to the intermediate depths, but returned to the surface and retarded ice growth throughout winter. Two different approaches were used to estimate the ocean heat fluxes; (i) a residual method based on a 1‐D thermodynamic ice growth model and (ii) a bulk parameterization using friction velocities and available heat content of water beneath the ice. The average heat flux in the inner YS varied from 13 W m−2 in October–December to less than 2 W m−2 in January–May. An average heat flux of 9 W m−2 was calculated for the outer YS. Moreover, we show that the upward heat flux in the outer fjord is strongly modulated by surface outflow, which produced two maxima in heat flux (up to 18–24 W m−2) during 26 December to 27 January and from 11 February to 14 March. By May 2014, the upward ocean heat flux reduced the landfast ice thickness by 18% and 24% in the inner and outer YS, respectively.